Safety and Efficacy of a New Endocapsular Device Used in Age-Related Cataract Surgery: Twelve-Month Follow-Up - Pallikaris, Ioannis G.; Elmassry, Ahmed; Ginis, Harilaos S.; Leonidou, Loukia L.; Sahin, Onurcan; Modatsos, Manolis; Liakopoulos, Dimitris; Elbassiouny, Shaimaa; Pallikaris, Aristofanis (ASSOC RESEARCH VISION OPHTHALMOLOGY INC, 2026)
Purpose: To evaluate the safety and efficacy of a novel endocapsular device used during cataract surgery at the 12-month follow-up. Methods: A cohort study was conducted in a university-affiliated private practice. Adults with age-related cataracts, intraocular lens power between 14 and 26 diopters, and no other ocular pathology were included prospectively. Exclusion criteria included diabetes, previous ocular surgery, cardiac conditions, and autoimmune diseases. One eye per patient was randomly assigned to receive the device before intraocular lens implantation. Follow-ups were conducted preoperatively and at 1 day, 1 week, and 1, 3, 6, and 12 months postoperatively. The primary safety endpoint was the incidence of adverse events; the primary efficacy endpoint was the incidence of posterior capsule opacification (PCO) postoperatively at 12 months. A control group was formed retrospectively for comparison of PCO at 12 months. Spherical equivalent, corrected distance visual acuity, and intraocular pressure were also measured. Results: A total of 121 patients were enrolled. Sixteen adverse events occurred in 12 patients; all resolved and were deemed unrelated to the device. PCO incidence at 12 months was 0.83% in the experimental group vs. 13.0% in the control group. The spherical equivalent stabilized by 3 months. At 12 months, the mean corrected distance visual acuity and intraocular pressure were 0.03 +/- 0.07 logarithm of the minimum angle of resolution and 11.23 +/- 2.03 mm Hg, respectively. Conclusions: The new device seems to be safe and have a beneficial impact on PCO up to at least 12 months postoperatively. Translational Relevance: We report our experience with a novel, safe, endocapsular open capsule device that shows promise in preventing posterior capsule opacification in real-world clinical settings.
Keywords: endocapsular device; cataract surgery; posterior capsular opacification; refractive stability; intraocular lens; POSTERIOR CAPSULE OPACIFICATION; ACCOMMODATING INTRAOCULAR-LENS; REFRACTIVE OUTCOMES; BAG OPACIFICATION; VISUAL OUTCOMES; PREVENTION; ANTERIOR; RING; IMPLANTATION; MULTICENTER; Ophthalmology